Mégapoles, polyrhythmy, porosity. Tracing ideas of Mediterranean urbanity in western scholarly discourse. - Baumeister, Martin (Routledge, 2021)
As a core concept of 20th-century urbanism in debates about urban crisis and renewal, “urbanity” bundles different, at times contradictory, ideas about the “good city” and “good urban life.” Depending on varying political, social or economic interests and constellations, it was always imbued with historical notions related to a strongly Occidental imagination going back to the classical Mediterranean world as the quintessential site of origin of Western civilization. This article looks for the “Mediterranean flavor” inherent in the ideas of “urbanity” in the context of urban debates in the 20th-century Western world. It considers how elements of the idea of a “Mediterranean urbanity” contributed to defining a particular type of city in the Mediterranean region. And finally, it asks for a reevaluation of this idea to study Mediterranean cities as laboratories for discussing and realizing “good” urban life.
Keywords: Urbanität; Stadtleben; Wertvorstellung; Zivilisation; Urbanismus; Regionale Disparität; Lebensqualität; Hafenstadt; Stadttyp; Ideologie; Stadtwissenschaft; Stadtgeschichte; Diskurs; Westliche Welt; Abendland